Pemberdayaan Kelompok Wanita Tani Sri Rejeki pada Pengolahan Sediaan Umbi Bawang Dayak (Eleutherine bulbosa Urb.): Empowerment of Sri Rejeki Farmer Women’s Group on Preparation of Dayak Onion Bulb Form (Eleutherine bulbosa Urb.) - Rahmi Muthia; Depy Oktapian Akbar; Aristha Novyra Putri; Dita Ayulia Dwi Sandi; Vebruati Vebruati; Revi Kunmariana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
One form of traditional health development is the development of medicinal plants. Not many community groups are currently aware of applied technology in terms of postharvest processed into simplicia (medicine raw materials) or other processed preparations. Sri Rejeki Farmer Women’s Group (KWT Sri Rejeki) in the Landasan Ulin Village, Liang Anggang District, is a group of women who cultivate vegetables and plants that can be used as medicinal plants, one of which is Dayak onion (Eleutherine bulbosa Urb). The activity carried out by KWT Sri Rejeki had only been in the form of planted plants, which were then sold in fresh form. This community dedication aimed to educate the public, especially KWT Sri Rejeki, regarding the efficacy of Dayak onion bulb plants. It optimized the use of cultivation and processed plants into traditional medicinal preparations with economic value. The method used was site review and plant data collection from KWT Sri Rejeki, education on the efficacy of Dayak onion bulbs, training on processed dayak onion bulbs into simplicia, and training on processing dayak onion bulbs into dye preparations. The data collection results were Dayak onions selected as a typical Kalimantan plant to be developed, with the efficacy as an immunomodulator. Dayak onion bulbs that will be designed were processed into simplicia which were then made into dye preparations and packaged. The processing of simplicia and preparations for dipping Dayak onion bulbs can be done independently by the members of the KWT Sri Rejeki.